Changing the old way of Thinking : Geling Yan's The Thirteen Flowers of Nianjing in a Postcolonial Frame - Haidar Laique Hashim (مجلة الباحث, 2026)
Although formally considered as a novella, The Thirteen Flowers of Nanjing attains a scope and depth comparable to that of a novel through its concentrated engagement with essential events during the Japanese invasion. This study moves beyond the dominant historical readings of the text to foreground its potent, yet critically overlooked, postcolonial dimension—a dimension carefully rooted by the author from the opening pages. Through a postcolonial analysis, this research examines key narrative episodes to demonstrate how the novella articulates a resistance narrative not through conventional opposition, but through sacrifice and resurrection. Specifically, it argues that the subaltern—particularly women—becomes the vehicle through which the colonized Chinese nation “writes back,” asserting agency and cultural resilience.